Family Business and Digital Transformation - Daskalopoulos, Efthymios (2025)
Family firms are at an intertidal moment. Traditionally highly adaptable and resilient entities, defined by the family's involvement on multiple levels, family firms can either leverage their unique characteristics and transform in the digital era or fall prey to their inefficiencies. Surprisingly, even though digital transformation belongs to widely discussed themes in current management science, when it comes to investigating the phenomena of the most prevalent organisational form of businesses - family firms - the literature has been relatively silent. This dissertation provides theoretical and empirical insights into the business context of family firms competing in the current era of digital transformation and AI technologies. It comprises four interrelated articles employing a mix of methodologies: a review, a conceptual paper, and two quantitative studies. Through an analysis of the relevant peer-reviewed articles on the intersection between digital transformation and family business, the article identifies a central scholarly perspective: family businesses, often considered resource-constrained, possess unique assets and exhibit a distinctive ability to develop new capabilities which can play a significant role in navigating digital transformation and AI technologies. Building on the resource-based view, the second article conceptually develops the concept of family slack, defining the subdimensions of distinctive resources above the minimum necessary to produce a given organisational or performance output level and connecting them with possible drivers of digital transformation.